HISTORIOGRAPHY OF MADRASAHS BUILT BY AMIR TEMUR AND TEMURIZA'S RULERS - Mamatkulova Farangis Orzukulovna (American Journals Publishing, 2023)
By the time of Timur, when Samarkand became a place of scholars, the functions of the madrasah had expanded and they had become high-level scientific institutions. Many scholars taught students in the Samarkand madrasas, which were established and flourished during the time of Timur and before Timur. In addition to religious values, the madrasah also began to train civil servants and talented young scientists. An example of this is the fact that Ibn Arabshah, a young scholar brought from Damascus, studied at the Idiku Temur Madrasah in Samarkand and became a renowned historian and scholar. This article describes the source study of madrasahs built during the period of Amir Temur and the Timurids.
Keywords: Statesmen, Talented commanders, Major politicians, Fur Traders Mosque, Darbi Oliya, Mirzoi caravanserai, Kosh madrasah, Giyosul-lugot, observatory, Ulugbek academy.